The examination of factors relating to the leadership style of nursing leaders in hospitals - Lorber, Mateja (Naše gospodarstvo, 2016)
Theories often describe leadership with different classifications, based on personality and behaviour, and have been used to establish the traits and behaviours that determine an effective leadership style. We used the quantitative methodology to investigate the determinants of the leadership style among nursing leaders in Slovene hospitals. Based on the results, we determined that demographic characteristics such as gender, age, length of employment, and level of education do not affect the choice of the leadership style. Internal organizational characteristics such as job position, emotional intelligence, communication, personal characteristics, and the decision-making process are positively associated with the leadership style. Personal characteristics are considered important when it comes to using specific leadership styles, regardless of the choice of the leadership style, which also depends on the situation and external influences.
Keywords: bolnišnice; čustvena inteligentnost; psihologija osebnosti; vodenje; zdravstvena nega